Sexual Rejection Model in Prevention of Pre-Marital Sexual Adolescent Girl in Banjarmasin City: A Cross Sectional Study - Qariati, Nurul Indah; Salim, Lutfi Agus; Indriani, Diah; Indah, Meilya Farika; Asrinawaty, Asrinawaty (Journal of Posthumanism, 2025)
Adolescents represent the backbone of a nation’s future, yet misconduct among young women poses risks such as early pregnancy, abortion, stunted birth, and HIV/AIDS. This study leverages the Health Promotion Model (HPM) to explore factors influencing sexual rejection and the prevention of premarital sexual behavior. Conducted between August and October 2023 in Banjarmasin City, the research involved 147 high school girls selected via stratified random sampling, adhering to ethical guidelines and pa-rental consent for minors. Key variables examined include age, dating history, knowledge, religiosity, perceived benefits, barriers, self-efficacy, and activity-related affect, alongside media exposure, commitment, and interpersonal influences from parents and the environment. Findings revealed significant associations between knowledge, religiosity, and cognitive factors like self-efficacy and activity-related af-fect, which influence sexual rejection. Media exposure, commitment, and interpersonal factors also emerged as pivotal. The study underscores the critical role of individual characteristics, specific behaviors, cognitive aspects, and immediate competing de-mands in fostering sexual rejection. It calls for robust support from families, communi-ties, and governments to promote reproductive health awareness, sexuality education, and self-restraint, equipping adolescents with persuasive communication skills to navigate challenges and prevent premarital sexual behavior.